Analisis Perbandingan Efisiensi Pembiayaan BUS dengan BPRS di Jawa Barat Tahun 2017-2019 - Islami, Jasmin Bunga; Supriyanto, Trisiladi; Sari, Lili Puspita (UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
The development of Islamic banking in Indonesia is increasingly progressing quite rapidly. This development is evidenced by the increasing total number of Islamic commercial banks, as well as the very large number of Islamic people's financing banks. This study aims to investigate the comparison between BUS and BPRS. This study uses a quantitative methodology with data analysis techniques using Data Envelopment Analysis (DEA), and a different test using an independent sample t-test. The population used is 5 Islamic Commercial Banks (BUS) and 5 Sharia People's Financing Banks (BPRS) in West Java with data samples of fixed assets, savings, operational costs, financing, and operating profit. This study uses secondary data sourced from the official website of the Financial Services Authority. The results of this study are that BPRS has a higher average efficiency level than BUS, and there is no significant difference between BUS efficiency and BPRS in 2017, 2018, and 2019 based on DEA CRS and DEA VRS.Berkembangnya perbankan syariah di Indonesia semakin memiliki kemajuan yang cukup pesat. Perkembangan ini dibuktikan dari angka total bank umum syariah yang meningkat, serta angka bank pembiayaan rakyat syariah yang berjumlah sangat besar. Penelitian ini bertujuan menginvestigasi perbandingan antara BUS dengan BPRS. Penelitian ini memakai metodologi kuantitatif dengan teknik analisis data memakai Data Envelopment Analysis (DEA), serta uji beda menggunakan sampel independent t test. Populasi yang digunakan adalah lima Bank Umum Syariah (BUS) dan lima Bank Pembiayaan Rakyat Syariah (BPRS) di Jawa Barat dengan sampel data aset tetap, simpanan, biaya operasional, pembiayaan, dan laba operasional, kemudian data sekunder yang bersumber dari website resmi Otoritas Jasa Keuangan. Hasil dari penelitian menjelaskan bahwa BPRS memiliki rata-rata tingkat efisiensi yang lebih tinggi dibandingkan dengan BUS, serta tidak terdapatnya perbedaan yang signifikan antara efisiensi BUS dengan BPRS pada tahun 2017, 2018, dan 2019 berdasarkan DEA CRS maupun DEA VRS.